HUBUNGAN TEKANAN INTRAOKULAR DENGAN STADIUM PRIMARY OPEN-ANGLE GLAUCOMA DI RSUP DR M DJAMIL PADANG TAHUN 2019-2021 - Putri, Dira Afrelia; Ilahi, Fitratul; Ihsan, Indra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Primary open-angle glaucoma (POAG) is a progressive chronic optic neuropathy that often affects adults with characteristics of optic nerve damage in the eye due to increased intraocular pressure (IOP). POAG is characterized by an open anterior chamber angle. POAG with increased IOP is understood to mean decreased outflow of aqueous humor due to increased resistance to such outflow. This study aims to determine the association between intraocular pressure and stage of primary open-angle glaucoma. This study is an analytic study with a cross sectional approach using retrospective data. The sampling technique used was total sampling, in which all subjects who met the inclusion and exclusion criteria were selected as a sample of 84 eye samples. Analysis of the data used in the form of univariate analysis and bivariate analysis using Spearman correlation test. POAG is more common in women (55,6%). The majority of POAG experienced by the age group over 40 years (95,6%). There is a significant relationship between IOP and stage of POAG (p=0.001) with medium correlation strength and positive correlation direction (r=0,371). There is a relationship between IOP and POAG with a positive correlation direction, where the higher the IOP value, the POAG stage will increase.